2016
DOI: 10.1007/s11274-016-2028-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage biocontrol in wastewater treatment

Abstract: Waterborne bacterial pathogens in wastewater remains an important public health concern, not only because of the environmental damage, morbidity and mortality that they cause, but also due to the high cost of disinfecting wastewater by using physical and chemical methods in treatment plants. Bacteriophages are proposed as bacterial pathogen indicators and as an alternative biological method for wastewater treatment. Phage biocontrol in large scale treatment requires adaptive and aggressive phages that are able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 70 publications
0
52
0
1
Order By: Relevance
“…In current scenario, broad-spectrum antibiotics are used for killing pathogenic bacteria, in different sectors such as health, agriculture, and waste treatment, etc. (Jassim et al, 2016). The action of these broad-spectrum antibiotics is not specific; they kill other nonpathogenic bacterial populations and their repeated application develops antibiotic-resistant bacterial strains.…”
Section: Bacteriophage For Pathogen Reduction In Wastewatermentioning
confidence: 99%
See 3 more Smart Citations
“…In current scenario, broad-spectrum antibiotics are used for killing pathogenic bacteria, in different sectors such as health, agriculture, and waste treatment, etc. (Jassim et al, 2016). The action of these broad-spectrum antibiotics is not specific; they kill other nonpathogenic bacterial populations and their repeated application develops antibiotic-resistant bacterial strains.…”
Section: Bacteriophage For Pathogen Reduction In Wastewatermentioning
confidence: 99%
“…As a consequence of this, many bacterial infections and surgeries become more dangerous because of the spread of antibiotic-resistant bacteria. Therefore, phages emerge as a potential biocontrol agent against many multidrug-resistant strains of bacteria (Jassim et al, 2016;Mulani et al, 2015).…”
Section: Bacteriophage For Pathogen Reduction In Wastewatermentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports have revealed that 70% of the world's bacteria have now developed a resistance to antibiotics, including those drugs regarded as our last line of defence which were carelessly sprayed over fields and livestock and have now polluted waterways Jassim et al 2016). As a consequence of this, many common infections will no longer have a cure and hospital surgeries are more dangerous due to the spread of hospital acquired bacteria which are resistant to antibiotics.…”
Section: Antibiotic-resistant Bacteria As Potential Agents Of Bioterrmentioning
confidence: 99%